A systematic literature review of critical success factors and barriers in lean supply chain management - Hamizah Pardi,; Mohd Nizam Ab Rahman,; Nizaroyani Saibani,; Ariff Azly Muhamed, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The objective of this study is to conduct a systematic literature review to identify the barriers and critical success factor that influence in implementation of Lean Supply Chain Management (LSCM) practices in industry. Through this systematic literature review (SLR), it is expected to identify the main gaps related to LSCM implementation in industry and discuss the relevance of research in this topic for indicating the future research direction. A SLR was developed and determined, which involved the selecting of keyword, developing of research question, searching and evaluation of literature for 53 research articles. The content of present of literature was reviewed, critically analysed and synthesised from the perspective of barrier and critical success factors that influence the implementation of LSCM. This study reveals that relationship with supplier, commitment and support by top management are the key critical success factor in lean implementation. Furthermore, the results showed that lack of management commitment and leadership, lack of training and skills, lack of system view or strategy are the barriers in lean implementation. Based on the extensive systematic review of literature, we found of the consistency data between Barriers and Critical Success Factor. This study extends previous studies on LSCM, strengthens the body of knowledge on the issue and consolidates the key LSCM activities, barriers and critical success factors associated with its implementation. The clear identification of these topics can allow researchers and practitioners to predict occasional problems and to set the right standards for the implementation of LSCM.